The reality of suffering from Professional pressures among nurses A field study at Mohammed Siddik ben Yahya Hospital in the province of Jijel. - Mjider, Billel (Journal of Human Sciences, 2021)
The study aimed to find out the reality of suffering from Professional pressures among nurses, through a field study on a group of nurses in Mohammed Siddik ben Yahya Hospital in the wilaya of Jijel on 97 nurses from different departments to detect the most important factors that lead to the emergence of various pressures in the field of nursing as well as to detect their effects Psychological and social to nurses. We have designed a questionnaire that measures the pressure applied to the research sample and found that the pressure of the nature of work and social pressures came first in the view of nurses, in addition to overcrowding and the large number of patients and the lack of medicines and medical equipment and the lack of security protection and exposure to many Attacks and privacy of dealing with some serious diseases and their families and relational problems with them, in addition to physical and physical pressures as well as the injustice of the sector officials in the design of a wage system adapted to the nature of the work of large nurses in addition to the nature of work, especially night shift In addition to the risks to nurses who work in the interest of radiology and the cause of various occupational diseases, which creates them very great pressure.